Inovativnost v stanovanjskem načrtovanju in v urejanju prostora - Mlinar, Zdravko (Annales. Series historia et sociologia, 2009)
As the world is growing increasingly open (informatization, globalization), there is more and more place for innovation in housing design and organization of space. The inclusion of Slovenia into Europan, the European organization of young architects and urban planners, provided a way to gather a wealth of ideas concerning housing design and organization of space for various programmes in the Livade-west area in Iyola. A total of fifty projects was submitted, representing the highest number of participants from all over Europe taking part in a single competition in Slovenia so far. Young experts envisioned different ways to reach beyond the disadvantages of mono-functional housing quarters and to create a spatial arrangement, which would encourage a livelier mode of urban life. Their attention was focused on the typical traits of the Mediterranean environment, particularly the relationship between public, half-public and private space. Generally, the solutions would give a high priority to spaces, which enable and encourage social interaction of residents. However, though they produced innovative and variable schemes of bringing together and intertwining public, half-public and private spaces, they would usually not devote much attention to potential impairment of privacy in residential spaces. Suggested solutions pay regard to social-developmental trends like the increasing diversity of lifestyles and the increasing social and spatial mobility of the population, which demands certain flexibility of the urban structure. However, when looking at the past, some authors regard the continuity as overwhelmingly self-evident and do not consider the fact, that the same spatially-physical arrangements do not produce the same effects today as they did in the past. In general, not enough attention is devoted to the fact, that the space itself is not (any longer) a decisive factor, but has become of secondary significance compared to the increasing number and diversity of interests. The lack of knowledge about the sociological findings concerning social contacts in space and desired and undesired effects of informal social control is evident. On one hand Europan opens the sphere of new ideas and brings about the enrichment of the practice of building mono-functional housing quarters, which had prevailed in the recent past. On the other hand it remains predominantly limited to the architectural aspect and enclosed within the logical frame of the physical structure of construction while neglecting the novelties of the information age. The failure to realize the best and awarded Europan solutions in Slovenia and elsewhere brings attention to urban actors and their interests. So far, this has not been considered as an expert field or has been considered to belong to other fields of research (economy, sociology). Along with the need for more intensive inclusion into Europan at the level of the state and individual municipalities, there will be a greater need for: 1. critical (interdisciplinary) expert response to baseless general starting points and 2. exhaustive determination and disclosure of typical domestic, local traits, which can influence the action of participants, who do not know them
Keywords: Europan; Izola; javni prostor; privacy; prostorsko planiranje; Slovenia; Slovenija; spatial planning; stanovanjska naselja; urbana sociologija; urbanism; urbanizem; ustvarjalno okolje; zasebnost